Anticipating White Futures: The Ends‐Based Orientation of White Thinking. Issue 1 (29th June 2021) - Mueller, Jennifer C.; Washington, DyAnna K.
Abstract : Recent scholarship demonstrates that whites' racist action requires creativity as much as habit. Racial cognition is implicated in this behavior, as white people use ignorance and apathy to overcome epistemic challenges that threaten white power, privilege, and wealth. Using Mueller's Theory of Racial Ignorance, we show how these cognitive processes abide by an ends‐based orientation —one whereby white people coordinate "anticipated futures" to maintain the literal and psychic spoils of racism. Analyzing papers produced by white undergraduates following a project investigating systemic racism and family wealth transmission, we reveal how students' practical takeaways betray this ends‐based orientation, which remains resilient amidst critical learning.